2009
DOI: 10.51936/atfk8407
|View full text |Cite
|
Sign up to set email alerts
|

Social support network and received support at stressful events

Abstract: Many studies in the field of social support (e.g., Hobfoll, 1985; Thoits, 1985; Cutrona and Russell, 1990; Kienan, 1997) show that the effectiveness of a certain type of provided support and mechanisms by which the support works are often highly dependent on a specific situation, where support is needed. For instance, emotional support may be provided in a situation (e.g., an accident), where an affected person needs or expects help of a more practical kind. The provided unsuitable type of support may thus cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…PSS is an individual's perception that social support would be obtained when needed (Hlebec, Mrzel, & Kogovšek, 2009). Perceived social support gives individuals a sense of acceptance that they are valued and cared for (Cao et al, 2019).…”
Section: Perceived Social Support (Pss)mentioning
confidence: 99%
“…PSS is an individual's perception that social support would be obtained when needed (Hlebec, Mrzel, & Kogovšek, 2009). Perceived social support gives individuals a sense of acceptance that they are valued and cared for (Cao et al, 2019).…”
Section: Perceived Social Support (Pss)mentioning
confidence: 99%
“… 14 – 16 The research on social support can be divided into two perspectives: sociological and psychological perspectives. The former emphasizes that social support network is the source where individuals obtain support, 17 while the latter focus on the personal feelings and perceptions of those supported. 18 …”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…[14][15][16] The research on social support can be divided into two perspectives: sociological and psychological perspectives. The former emphasizes that social support network is the source where individuals obtain support, 17 while the latter focus on the personal feelings and perceptions of those supported. 18 Social support network is a special form of the social network, so we need to understand social support network in the context of social network.…”
Section: Social Networking and Its Development In The Age Of Social M...mentioning
confidence: 99%
“…network results, since support from them was quite negligible in our target groups of partners, 8 disregarding the presence of coworkers might be a limitation according to some types of support. For instance Hlebec et al (2009) showed that coworkers are providing support to ego especially in work situations (such as difficulties with the boss or changes at the workplace), but not in case of health problems, changes or difficult situations where friends and kin provide much more support. McPherson et al (2006) and Dahlin et al (2008) showed that coworkers may be a source of emotional support (more specifically, they are people to whom ego talks about personal matters).…”
Section: Constructing the Network Of Italians Living In Couplementioning
confidence: 99%